Modelling sugarcane vinasse processing in an acidogenic reactor to produce hydrogen with an ADM1-based model. (28th February 2020) - Couto, P.T.; Eng, F.; Naessens, W.; Nopens, I.; Zaiat, M.; Ribeiro, R.
Abstract: Biohydrogen can be produced by dark fermentation of sugarcane vinasse, wastewater from the sugar-alcohol industry, in acidogenic anaerobic bioreactors. In this work, a model based on ADM1 was constructed to model anaerobic processing of sugarcane vinasse in an acidogenic batch reactor. Based on experimental data, hypotheses were put forward. Two new pathways were assumed: A c e t a t e + L a c t a t e → B u t y r a t e + H y d r o g e n and G l y c e r o l → B u t y r a t e + H y d r o g e n . A sensitivity analysis was carried out to reduce the number of free parameters, after which the model was calibrated with the experimental data. The proposed model was able to adequately describe sugar and glycerol consumption, acetate and lactate production and consumption and hydrogen and butyrate production over the operational time at an initial concentration of vinasse of 30 k g C O D m − 3 . Nevertheless more improvements can be carried out to make the model more realistic and to cover intermediate metabolic pathways under conditions of lower vinasse concentration, such as 15 k g C O D m − 3 and 20 k g C O D m − 3 . Highlights: An ADM1-based model was constructed to simulate an acidogenic reactor. Two new metabolic pathways were added to the model. The number of free parameters was reduced using a sensitivity analysis. The model suitably described the behavior of substrates and products for 30 kgCODm −3 . Better and constant hydrogen production was observed under 30 kgCODm −3 of vinasse.